UPAYA MENGURANGI PENIPISAN LAPISAN OZON - Widowati Widowati; Sutoyo Sutoyo (BUANA SAINS, 2009)
Ozone is one of the constituent gases of the atmosphere. This gas is concentrated in the stratosphere layer functions as a UV filter so as not to cause damage on the surface of the earth. This layer of ozone in most produced by the reaction of oxygen with ultraviolet light. Ozone in the troposphere is the layer of air pollutants and harmful to the respiratory system of human, animal and plant metabolism. The presence of ozone in Earth's atmosphere in low concentrations throughout the year. Decreased concentration or the ozone layer depletion triggered by the compounds of CFCs (Chloro Fluoro Carbon) and ODS (Ozone depleting Subsantance). ODS compounds include nitrogen oxide (N2O) is a byproduct of combustion, methyl bromide, carbon tetrachlorida and methyl chloroform. To determine the thickness of the ozone layer is measured by satellite instruments or Nimbus-7 satellite instruments EP-toms. Total concentration of atmospheric ozone standard can be determined using the unit DU (Dobson Unit). Concentration at a point can also be measured in units of ppb (parts per billion) or in μg.m³. Efforts to reduce ozone layer depletion, among others, regularly measure the thickness of the ozone, suppress the use of CFC compounds that are widely used as refrigrant in freezers, refrigerators, room air conditioning and engine cooling, spray cans for air freshener, perfumes, solvents, foam developers and reduce the use of ODS substances which have been agreed by the international community through the Montreal Protocol, Canada in 1987